Tensile bond strength of ceramics luted to composite resin core materials / Sura Mohammed Abdulrazzaq Al-Janabi - Al-Janabi, Sura Mohammed Abdulrazzaq (2012)
Objective: The objective of this study was to evaluate the tensile bond strength of Vita In-Ceram® Zirconia coping Materials when luted to two different composite resin core materials with four different luting materials. Methods: One hundred and twenty ceramic specimens (8X5mm) were fabricated from a Vita In-Ceram® Zirconia kit which was prepared in a ceramic dental laboratory according the manufacturer’s instructions. One hundred and twenty composite resin specimens were prepared from Spectrum®TPH®3 (hybrid composite) (Dentsply, Germany) (n=60) and Composan Core DC (flowable composite) (Promedica, Germany) (n=60). The ceramic discs were divided into eight groups (n=15 for each): group 1: (Control) ceramic cemented to Spectrum®TPH®3 with Elite (GC Corp, Japan); group 2: ceramic cemented to Spectrum®TPH®3 with Fuji I (GC Corp, Japan); group 3: ceramic cemented to spectrum®TPH®3 with Calibra® (Dentsply, Germany); group 4: ceramic cemented to Spectrum®TPH®3 with PanaviaF 2.0 (Kuraray Med Inc., Japan); group 5: (Control) Ceramic cemented to Composan Core DC with Elite; group 6: Ceramic cemented to Composan Core DC with Fuji I; group 7: Ceramic cemented to Composan Core DC with Calibra®; group 8: Ceramic cemented to Composan Core DC with PanaviaF 2.0. The specimens were stored for 24 hours in distilled water at 37 C prior to tensile bond strength testing. The data for each group were analyzed by the Kruskal-Wallis test followed by multiple pair-wise comparisons by using Mann-Whitney rank sum test for independent samples, (p < 0.05). Significance levels were adjusted with the Bonferroni correction for multiple testing. The fracture interfaces on each specimens were examined under a stereomicroscope to classify the mode of failure.